2022
DOI: 10.1177/27523810221127596
|View full text |Cite
|
Sign up to set email alerts
|

Representation and diversity in the sign language translation and interpreting profession in the United Kingdom

Abstract: This article reports the findings of a nationwide sign language translator and interpreter (SLTI) census to establish a baseline description of the United Kingdom’s SLTI workforce that was commissioned by the Association of Sign Language Interpreters UK. Complete responses were received from 690 practitioners from across the United Kingdom (43% of the potential sample). The survey responses were analysed using the SPSS statistical software, specifically to look at various intersectional characteristics concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…A total of 25 DI participants (46% of the target population) completed the survey. This is comparable with the results of Napier et al (2022), who reported a 43% response rate to their demographic survey of sign language interpreters in the United Kingdom. This is an acceptable response rate for sampling professional groups (Baruch & Holtom, 2008; cited in Napier et al, 2022), and it enables a snapshot of current DI demographics in Canada.…”
Section: Survey Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…A total of 25 DI participants (46% of the target population) completed the survey. This is comparable with the results of Napier et al (2022), who reported a 43% response rate to their demographic survey of sign language interpreters in the United Kingdom. This is an acceptable response rate for sampling professional groups (Baruch & Holtom, 2008; cited in Napier et al, 2022), and it enables a snapshot of current DI demographics in Canada.…”
Section: Survey Findingssupporting
confidence: 86%
“…This is comparable with the results of Napier et al (2022), who reported a 43% response rate to their demographic survey of sign language interpreters in the United Kingdom. This is an acceptable response rate for sampling professional groups (Baruch & Holtom, 2008; cited in Napier et al, 2022), and it enables a snapshot of current DI demographics in Canada. Because the survey design and administration were intended to give all members of the DI population an equal opportunity to participate, even a relatively small sample size can yield results that accurately represent this population (Fogli & Herkenhoff, 2018).…”
Section: Survey Findingssupporting
confidence: 86%
“…The survey respondents were mostly female, reflecting the female-dominated sign language interpreting profession (Napier et al, 2022). Of the 331 respondents, 117 had 0–10 years of professional (paid) experience, 126 had 10–20 years of experience, and 88 had over 20 years of professional experience.…”
Section: Background and Methodologymentioning
confidence: 99%
“…In the FGD, JBIMs highlighted a potential bene t of the DITE app for the Deaf community in that the app offers a unique feature allowing patients to select JBIMs based on preferences related to race, gender, and potentially religion. This ensures that Deaf patients can choose interpreters who resonate with their own backgrounds, fostering a sense of representation and inclusivity [35]. This dedicated effort to promote equality, diversity, and inclusion within the Deaf patient community is particularly crucial in Malaysia's diverse, multiracial, and multireligious context.…”
Section: Equality Diversity and Inclusion In Jbim Selectionmentioning
confidence: 99%